A distant shore [compact disc, unabridged] : a novel - Kingsbury, Karen (Simon & Schuster Audio, 2021)
She was a child caught in a riptide in the Caribbean Sea. He was a teenager from the East Coast on vacation with his family. Ten years after he dove into the water to save her life, they meet again, and again, both their lives are on the line.